Uncertainty of Routine pH Measurements Evaluated by the Principle of Pooled Calibrations - Andersen, Jens Enevold Thaulov; Menong, Mercy (Universitas Islam Indonesia, 2025)
In the digital age, taking logarithms of data is no longer necessary when assessing pH measurement uncertainties. The focus is now on using raw, unaltered data. Routine pH measurements often differ from those in reference labs, so quantifying these differences is necessary. The uncertainties of pH values at 25°C were evaluated using mass-by-mass calculations, along with comparisons between two pH meters. Four buffer systems and several beverage samples were tested. Expanded uncertainties (U) of up to U = 0.36 were observed for pH values between 2 and 11, significantly higher than those reported by manufacturers. While measured pH values were slightly higher than calculated ones, overlapping confidence intervals allowed the data to be combined. Due to significant uncertainties, the reliable pH range was limited to 1 < pH < 11, potentially narrower (1 < pH < 6.5). Routine pH measurement uncertainties did not match those based on the PoPC, with notably high CV values for proton activities at pH values below the buffers' pKa.